Diverse subsistence strategies related to the spatial heterogeneity of local environments in the Hengduan Mountain Region during the Bronze Age - Lu, Minxia; Lu, Yongxiu; Yang, Zhijian; Cili, Nongbu; Ma, Minmin (Frontiers in Earth Science, 2023)
Human subsistence strategies in East Asia changed significantly during the Bronze Age. The notable spatial variability in these strategies has been mainly attributed to the asynchronous introduction and adoption of new crops and livestock, as well as climate changes. However, the impact of differential local environments on spatial patterns of subsistence strategies in diverse geomorphic areas, such as the Hengduan Mountain Region (HMR), is poorly understood. In this study, we present new carbon and nitrogen isotopic data of human bone collagen from the Adong and Gaozhai tombs in the HMR. Adong is located in a mountain area, and Gaozhai is located on a river terrace. Both sites were dated to the early third Millennium BP (before the present). Our results suggest that human diets at Gaozhai were dominated by C3 foods. Human diets at Adong, alternatively, displayed more differentiation, with greater consumption of C4 foods. Further evidence is needed to discuss the significant differences in δ15N values of human bone collagen between the Gaozhai and Adong tombs. By comparing published isotopic, archaeobotanical, and zooarchaeological data, as well as the altitude and precipitation at the archaeological sites, we propose that precipitation may have affected the diversity of human dietary strategies in the Bronze Age HMR. We conclude that at higher altitudes, humans adopted diverse subsistence strategies and obtained meat resources by hunting. Some of this preferential behavior is likely explained by the survival pressure in the highlands of the HMR during the Bronze Age.